Philosophy of Science Series: Harnessing the Multidisciplinary Edge Effect by Exploring Paradigms, Ontologies, Epistemologies, Axiologies, and Methodologies. (May 2020) - Varpio, Lara; MacLeod, Anna
Abstract : Health professions education (HPE) researchers come from many different academic traditions, from psychology to engineering to rhetoric. Trained in these traditions, HPE researchers engage in science and the building of new knowledge from different paradigmatic orientations. Collaborating across these traditions is particularly generative, a phenomenon the authors call the multidisciplinary edge effect . However, to harness this productivity, scholars need to understand their own paradigms and those of others so that collaboration can flourish. This Invited Commentary introduces the Philosophy of Science series—a collection of articles that introduce readers to 7 different paradigms that are frequently used in HPE research or that the authors suggest will be increasingly common in future studies. Each article in the collection presents a concise and accessible description of the main principles of a paradigm so that researchers can quickly grasp how these traditions differ from each other. In this introductory article, the authors define and illustrate key terms that are essential to understanding these traditions (i.e., paradigm, ontology, epistemology, methodology, and axiology) and explain the structure that each article in this series follows.